Perception and Use of Herbal Medicines Among Clients Visiting Selected Community Pharmacies in Ibadan, Nigeria (African Journal of Biomedical Research, 2020)
Globally, there is an increasing trend in the use of herbal medicines. Despite, the benefit of its use, herbal medicines are not completely harmless. This study aims to evaluate the perception and use of herbal medicines among clients who visited selected community pharmacies in Ibadan metropolis, Nigeria. A cross-sectional survey was carried out among clients who patronized the selected community pharmacies, using a self-administered questionnaire. Demographic information, as well as perception and use of herbal medicines were evaluated. Data were summarized with descriptive statistics while K-W test was used for ranked variables at P